Monocyte Function in the Fetus and the Preterm Neonate: Immaturity Combined with Functional Impairment - Zoe Iliodromiti; Anastasis Anastasiadis; Michail Varras; Kalliopi I. Pappa; Charalambos Siristatidis; Vassilios Bakoulas; George Mastorakos; Nikolaos Vrachnis (Mediators of Inflammation)
It is well known that the innate immunity system, involving the contribution of monocytes and macrophages, may dysfunction in fetuses and preterm neonates. Monocytes are capable of differentiating into dendritic cells (DCs) or into mucosal macrophages during certain infections and of producing inflammatory mediators such as TNF-α (tumor necrosis factor-alpha), nitric oxide, and reactive oxygen species. Fetuses as well as neonates are prone to infections as a result of a defective mechanism within the above mononuclear system. Monocyte function in fetuses and preterm neonates depends on the phagocytic and oxidative capacity of macrophages and their antigen-adhesion ability. Functional rather than anatomical impairment is probably the underlying cause, while a defective production of cytokines, such as TNF-α, IL-6 (Interleukin 6), IL-1β (Interleukin 1 beta), and G-CSF (Granulocyte Colony-Stimulating Factor), has also been involved. The insufficient production of the above inflammatory mediators and the phenomenon of endotoxin intolerance, which latter occurs during entry of any antigen into the premature neonate, place preterm neonates at higher risk for infections. Existing research data are herein presented which, however, are deficient and fragmental, this accounting for the fact that the precise pathophysiology of these disturbances is not yet fully clarified.